Physiological and physicochemical responses of 'Sai nam phueng' tangerine to commercial coatings - Pimjai Seehanam (2018)
Tangerine fruit cv. Sai Nam Phueng was coated with six commercial coatings: Citrashine, Fomesa, Citrosol AK, Supershine-C, Zivdar, and Perfect Shine. Fruit were coated using gloved hands and stored at room temperature (23 ± 3 8C) and 56% ± 5% relative humidity. Physiological and chemical properties were recorded on Days 0, 1, 4, 7, 10, and 13. All coated fruit had lower respiration rates, reduced weight loss, higher gloss, and better appearance than control fruit. Coatings somewhat increased total soluble solids levels, but had no major effects on pH, titratable acidity, or vitamin C contents. Among the various wax formulations, tangerines coated with Zivdar, and to a lesser extent Perfect Shine, had the highest internal O2and lowest internal CO2levels, resulting in the lowest juice ethanol levels. Application of other coatings, especially Citrosol AK and Supershine-C, resulted in enhanced accumulation of off-flavors and decreased sensory acceptability.